Peculiarities of biotic interactions in the soil system - Bella Striganova (Studia Ecologiae et Bioethicae)
The heterogeneity of the soil environment is an important factor in the taxonomic and ecological diversity of the soil animal population. The contribution of invertebrates to the formation of aerial space in mineral soil horizons, in the form of a stable system of biopores, is considered on the basis of the author’s original materials and literature data. Aerial space is the necessary condition for the life of aerobiotic forms in the mineral soil, which comprise the bulk of soil invertebrates belonging to meso- and macrofauna. Zoogenic mechanisms of the formation of soil pores and soil aggregates are analyzed. Pore walls and aggregate surfaces are populated by different groups of pedobionts. !e partial isolation of these loci decreases predation, which creates conditions for the maintenance of high diversity and abundance of animal populations in the restricted volume of the populated soil profile.